Research on same-phase parallel connection technology of submarine cable - Ruiyong Zhang; Lai Wei; Lei Huang; Shuguan Wu; Jianlong Yang (Energy Reports, 2023)
Offshore wind power generation has been developed rapidly. In order to improve the efficiency of offshore wind power generation, this paper studies the parallel connection of two same-phase cables of two-circuit of submarine cables. Firstly, the mathematical model of same-phase parallel connection of submarine cables is established, and the cable impedance matrix and the expression of cable current unbalance are obtained. Then, two parallel cable parallel schemes are selected for comparative analysis. The results show that the triangle parallel scheme is more suitable for same-phase parallel connection of submarine cables. In addition, this paper is optimized for the triangle parallel scheme. On this basis, the operation strategy of the cable combined with cable temperature is studied in this paper. Enables cables to carry higher currents and to operate longer overloads. This study is beneficial to provide recommendations for the laying of practical submarine cables.